Sumanene-functionalised bis(terpyridine)–ruthenium(ii) complexes showing photoinduced structural change and cation sensing. Issue 1 (22nd November 2022) - Han, Junyi; Yakiyama, Yumi; Takeda, Youhei; Sakurai, Hidehiro
Abstract : Ru(ii ) complexes with sumanene-functionalised terpyridine ligands exhibited dual emission via the TICT mechanism due to the relatively easy rotation around the sumanene–terpyridine bond axis. They also showed selective Li + sensing ability. Abstract : Four luminescent Ru(ii ) complexes (C1–C4 ) with sumanene-functionalised terpyridine ligands (L1 and L2 ) were synthesised. The presence of the sumanene moiety enabled the emergence of the ligand-centred emission and resulted in relatively easy rotation around the sumanene–terpyridine bond axis. These eventually resulted in the emergence of dual emission via the Twisted Intramolecular Charge Transfer (TICT) mechanism. This was initiated by the electron transfer from sumanene to the terpyridine–metal centre while absorbing a photon, and then the electron was converged by the electron back transfer to the phenyl moiety from the terpyridine–metal centre. Further experiments revealed the susceptible Li + sensing ability of the complexes, which was probably attributable to the cation–π interaction on the convex side of sumanene.